TRAUMATIC RIGHT DIAPHRAGMATIC HERNIA; A DELAYED PRESENTATION - Atif, Qurrat Al Ain; Khaliq, Tanwir (Journal of Ayub Medical College Abbottabad, 2016)
Diaphragmatic rupture following blunt or penetrating thoraco-abdominal trauma is frequently missed. It presents years later with herniation of abdominal viscera. Surgical treatment should be sought for when diagnosed. A 56 year old female presented to emergency with traumatic right diaphragmatic hernia, road traffic accident 8 years ago when she sustained multiple rib fractures on the right side. Upon diagnosis, successful primary hernia repair was performed. Non-specific clinical and radiological features of diaphragmatic hernia (diminished breath sounds, respiratory distress, orthopnoea, dyspnoea, hydro-pneumothorax, and mediastinal shift and lung collapse) lead to delayed or missed diagnosis. Patients present months to years later with complications. By including it in the differentials while managing a trauma patient along with collaboration of the radiology department, the chances of missing this finding would be lowered substantially. Keywords: Diaphragmatic hernia; Trauma; Intestinal obstruction